Impact of COVID-19 on cervical cancer screening: Challenges and opportunities to improving resilience and reduce disparities - Wentzensen, Nicolas; Clarke, Megan A.; Perkins, Rebecca B. (Preventive medicine, 2021)
The COVID-19 pandemic has a major impact on a wide range of health outcomes. Disruptions of elective health services related to cervical screening, management of abnormal screening test results, and treatment of precancers, may lead to increases in cervical cancer incidence and exacerbate existing health disparities. Modeling studies suggest that a short delay of cervical screening in subjects with previously negative HPV results has minor effects on cancer outcomes, while delay of management and treatment can lead to larger increases in cervical cancer. Several approaches can mitigate the effects of disruption of cervical screening and management. HPV-based screening has higher accuracy compared to cytology, and a negative HPV result provides longer reassurance against cervical cancer; further, HPV testing can be conducted from self-collected specimens. Self-collection expands the reach of screening to underserved populations who currently do not participate in screening. Self-collection and can also provide alternative screening approaches during the pandemic because testing can be supported by telehealth and specimens collected in the home, substantially reducing patient-provider contact and risk of COVID-19 exposure, and also expanding the reach of catch-up services to address backlogs of screening tests that accumulated during the pandemic. Risk-based management allows prioritizing management of patients at highest risk of cervical cancer while extending screening intervals for those at lowest risk. The pandemic provides important lessons for how to make cervical screening more resilient to disruptions and how to reduce cervical cancer disparities that may be exacerbated due to disruptions of health services. •The pandemic increases disparities in cervical cancer prevention.•HPV self-sampling can extend the reach of cervical screening.•Screening and management visits should be prioritized by risk.•The pandemic provides an opportunity to make cervical screening more resilient.